Citric acid aerospace stainless steel passivation: a green approach - Bragaglia, Mario; Cherubini, Valeria; Cacciotti, Ilaria; Rinaldi, Marianna; Mori, Stefano; Soltani, P.; Nanni, F.; Kaciulis, S.; Montesperelli, G. (Unknown, 2015)
Passivation is a common treatment to maximize the corrosion resistance of stainless steel. Nitric acid is generally used and involves several ecological problems, citric acid could be a promising and environmentally friendly alternative to nitric acid. In this work citric acid has been extracted from lemon waste using and eco- friendly procedure. The stainless steel samples have been treated in both nitric and citric acid (commercial and extracted) and corrosion test have been performed. The results show how citric acid can be used as substitute of nitric acid in passivation treatment.